Salaf and Khalaf Strategy: Improving Reading Skill the Heritage Book in Islamic Boarding School - Sanusi, Anwar; Mustofa, Ady Muh. Zainul (Universitas Muhammadiyah Sumatera Barat, 2024)
The ability to understand the heritage book is a fundamental thing a student must own in Islamic boarding schools. In their ability to read the heritage book, the students often find it difficult to read it, let alone understand it. But in understanding the heritage book, a student must have skills in understanding the grammatical Arabic (nahwu and sharaf) to read the heritage book. This study aims to determine the learning strategy for reading the heritage at the Islamic boarding school Al-Ittihad Cianjur. This study uses a phenomenological approach. This research belongs to qualitative research. Data collection is done by conducting observations, interviews, and documentation. Data analysis was carried out by reducing, presenting, and concluding data. The results showed: 1) Implementation of the learning strategy of the salaf and khalaf Islamic boarding schools at the Al-Ittihad Cianjur Islamic boarding school using the sorogan, bandongan, memorizing methods, giving mufradāt yaumiyyah (daily vocabulary), muhādasah yaumiyyah (daily conversation), heritage reading competition. 2) The reading ability of class XII students at the Al-Ittihad Cianjur Islamic boarding school is considered good because it is supported by learning Arabic in and outside the classroom. 3) Factors supporting the learning of the heritage book, namely the existence of teachers skilled in mastering the learning method, while the inhibiting factor for learning the heritage book is the level of student discipline is still low.